2022
DOI: 10.1177/10887679221081788
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Homicide Review Committees’ Recommendations and Impacts: A Systematic Review

Abstract: Domestic Violence Fatality Reviews/Domestic Homicide Reviews (DVFRs/DHRs) are multi-agency reviews aimed at reducing domestic homicides. This study systematically reviews research that examines DVFR/DHR recommendations, impact of these recommendations and proposals for improving DVFR/DHR processes. A narrative synthesis was adopted due to the diversity of the 11 studies reviewed. Themes identified from recommendations included: training and awareness; service provision and coordination; and recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
(162 reference statements)
0
15
0
Order By: Relevance
“…This is because domestic abuse-related deaths can be difficult to identify (Fairbairn et al, 2019). First, it can be difficult to determine what role domestic abuse may have played in a death by suicide (Jones et al, 2022). This is because, while there are established links between domestic abuse and suicidality, a direct causal contribution is hard to establish (McManus et al, 2022;Munro & Aitken, 2020).…”
Section: S-dardrs Are Under Conceptualisedmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because domestic abuse-related deaths can be difficult to identify (Fairbairn et al, 2019). First, it can be difficult to determine what role domestic abuse may have played in a death by suicide (Jones et al, 2022). This is because, while there are established links between domestic abuse and suicidality, a direct causal contribution is hard to establish (McManus et al, 2022;Munro & Aitken, 2020).…”
Section: S-dardrs Are Under Conceptualisedmentioning
confidence: 99%
“…Thus, effectively, S-DARDRs -unlike DHRs -are usually de-moored from the criminal justice system. Moreover, while a coroner may reach a verdict of suicide where there is sufficient evidence to suggest a victim intended to take their own life, such a determination may be challenging in terms of establishing a domestic abuse link (Jones et al, 2022). However, as with criminal justice, this may change: a coroner recently made this link when, for the first time in a coronial inquest, domestic abuse was identified as having a causal role in the death of Jessica 'Jessie' Laverack (Keynejad et al, 2022).…”
Section: S-dardrs Are (Usually) De-moored From the Criminal Justice S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns include, for example, the problematic recording of ethnicity data (Benbow et al, 2019;Chantler et al, 2020). Reflecting this, a systematic review examining 11 DHR/DVFR studies reported a common recommendation for standardised data collection (Jones et al, 2022). Another concern is the potential tensions around decision-making arising from differing disciplinary perspectives and/or power (Albright et al, 2013;Dale et al, 2017).…”
Section: Utilising Dhrs For Research Purposesmentioning
confidence: 99%